2023
DOI: 10.26565/2312-4334-2023-2-33
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Masking and Anti-Reflective SiO2 in Silicon Technology

Mykola S. Kukurudziak

Abstract: The article examines the problems of thermal oxidation of silicon. Oxidation plays an important role in planar technology, which in turn is the basis of the technology of silicon integrated circuits, photodetectors and other solid-state electronics. During our production of silicon p-i-n photodiodes, a number of systematic types of defects and deterioration of product parameters caused by the degradation of masking or anti-reflective coatings during the manufacturing process were observed. A decrease in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For the working wavelength of the described photodiodes, the anti-reflective oxide should be d SiO2 ≈0.18-0.19 μm [24]. When studying the thickness of the grown anti-reflective oxide in the two studied variants of photodiodes, it was found that the thickness of SiO 2 in PD [111] reaches d SiO2 ≈0.183 μm, and in PD [100] reaches d SiO2 ≈0.17 μm.…”
Section: B) Investigation Of Current Monochromatic Pulse Responsivity...mentioning
confidence: 99%
“…For the working wavelength of the described photodiodes, the anti-reflective oxide should be d SiO2 ≈0.18-0.19 μm [24]. When studying the thickness of the grown anti-reflective oxide in the two studied variants of photodiodes, it was found that the thickness of SiO 2 in PD [111] reaches d SiO2 ≈0.183 μm, and in PD [100] reaches d SiO2 ≈0.17 μm.…”
Section: B) Investigation Of Current Monochromatic Pulse Responsivity...mentioning
confidence: 99%